2018
DOI: 10.1051/matecconf/201820404015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of perforated concave delta winglet vortex generators on heat transfer augmentation of fluid flow inside a rectangular channel: An experimental study

Abstract: Compact heat exchanger with gas as a heat exchange medium is widely used in power plants, automotive, air conditioning, and others. However, the gas has a low thermal conductivity resulting in high thermal resistance causing a low rate of heat transfer. Therefore an improvement to the convection heat transfer coefficient is necessary. One way to enhance the convection heat transfer coefficient is to use a longitudinal vortex generator. However, the increase in convection heat transfer coefficient is followed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…It was found that the heat transfer rate inline array is much higher than the staggering array. Another experimental study is implemented by Syaiful et al [19] to show the effect of two types of VGs on heat transfer. Both types of VGs are placed in an inline position at angle of attack of 30.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the heat transfer rate inline array is much higher than the staggering array. Another experimental study is implemented by Syaiful et al [19] to show the effect of two types of VGs on heat transfer. Both types of VGs are placed in an inline position at angle of attack of 30.…”
Section: Introductionmentioning
confidence: 99%